2018
DOI: 10.1038/s41598-018-25378-9
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of epileptiform-like activity are generated in the sclerotic hippocampus from patients with drug-resistant temporal lobe epilepsy

Abstract: Human hippocampal slice preparations from patients with temporal lobe epilepsy (TLE) associated with hippocampal sclerosis (HS) are excellent material for the characterization of epileptiform-like activity. However, it is still unknown if hippocampal regions as cornu Ammonis (CA) 1, CA3 and CA4, generate population epileptiform-like activity. Here, we investigated epileptiform activities of the subiculum, CA1, CA2, CA3, CA4 (induced by elevation of extracellular potassium concentration) and the dentate gyrus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 63 publications
4
26
0
1
Order By: Relevance
“…3 A lack of knowledge on molecular mechanism of seizure initiation impedes the development of targeted seizure therapy, and modern antiseizure drugs therefore mostly target general brain excitability. [6][7][8][9][10][11] Similar seizure onset was also reported for most ex vivo animal models using various seizure-inducing protocols, [12][13][14] for human brain slices, [15][16][17] and for in vivo acute and chronic animal models. 5 The LVF activity pattern occurs in the majority of seizures and often starts with a high-amplitude spike (sentinel spike) followed by a pronounced DC shift.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…3 A lack of knowledge on molecular mechanism of seizure initiation impedes the development of targeted seizure therapy, and modern antiseizure drugs therefore mostly target general brain excitability. [6][7][8][9][10][11] Similar seizure onset was also reported for most ex vivo animal models using various seizure-inducing protocols, [12][13][14] for human brain slices, [15][16][17] and for in vivo acute and chronic animal models. 5 The LVF activity pattern occurs in the majority of seizures and often starts with a high-amplitude spike (sentinel spike) followed by a pronounced DC shift.…”
supporting
confidence: 59%
“…The LVF activity pattern occurs in the majority of seizures and often starts with a high‐amplitude spike (sentinel spike) followed by a pronounced DC shift . Similar seizure onset was also reported for most ex vivo animal models using various seizure‐inducing protocols, for human brain slices, and for in vivo acute and chronic animal models . The critical issue for understanding the seizure onset is what processes associated with the sentinel spike may trigger the following DC shift and the subsequent seizure.…”
supporting
confidence: 55%
“…Also, a study of resected human sclerotic hippocampal tissue found that sustained ictal‐like events were almost never recorded in the CA territories (Reyes‐Garcia et al . ). We have yet to explore the subicular and parasubicular territories.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, slices that also included entorhinal cortex and neocortical territories showed ictal-like events relayed into the hippocampus from the entorhinal cortex. Also, a study of resected human sclerotic hippocampal tissue found that sustained ictal-like events were almost never recorded in the CA territories (Reyes-Garcia et al 2018). We have yet to explore the subicular and parasubicular territories.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampal formation is characterized by a heterogeneous regional and laminar cyto-and receptorarchitecture which is tightly associated with segregated input, output and intrinsic fibre systems. Furthermore, the different hippocampal regions and/or layers are differentially involved in diverse aspects of memory formation and retrieval processes (Hunsaker et al 2008;Ji and Maren 2008;Bartsch et al 2011;Coras et al 2014;Ledergerber and Moser 2017;Roy et al 2017), and display a selective vulnerability to disease (Thal et al 2000;Braak et al 2006;Kerchner et al 2012;Reyes-Garcia et al 2018), as well as differential responses to pharmacological interventions and to endogenous substances (Lynch and Bliss 1986;Yamada et al 2003;Kobayashi et al 2004;Knox et al 2011;Trieu et al 2015). However, the exact mechanisms by which the specific molecular structure and wiring pattern of a hippocampal region underpins its functionality remain elusive.…”
Section: Discussionmentioning
confidence: 99%